MEDIA SOSIAL SEBAGAI SARANA MISI ALLAH: SEBUAH PENDEKATAN KONTEKSTUAL DI ERA DIGITAL - Sarai, Nathalia Sofia (TENTIRO: Jurnal Pendidikan dan Kesehatan, 2025)
Social media plays an important role in carrying out God's mission in the digital age. Platforms such as YouTube, Instagram, and podcasts are used to convey the Gospel creatively, interactively, and contextually, especially to the Millennial and Gen Z generations. The Gospel message can reach a wide audience without time and place constraints. However, the use of this media also requires the application of digital ethics and proper theological understanding so that the message conveyed remains in line with Christian values and is not misused. Therefore, the church must plan a good digital strategy and guidance for its congregation.